Identification and evaluation of the critical success factors for construction projects in Lithuania: AHP approach - Gudienė, Neringa; Banaitis, Audrius; Podvezko, Valentinas; Banaitienė, Nerija (Journal of Civil Engineering and Management, 2014)
This paper proposes the Analytic Hierarchy Process (AHP) as a tool to rank different critical success factors (CSFs) for construction projects in Lithuania. Considering the current lack of understanding of CSFs within the local context, this study is one of the first attempts to gain an understanding of the CSFs in the local industry. Our study revealed that, for construction projects in Lithuania, clear and realistic project goals, project planning, the project manager’s competence, relevant past experience of the project management/team, the competence of the project management/team, clear and precise goals/objectives of the client, the project’s value, the project’s complexity and uniqueness, the project manager’s experience, and the client’s ability to make timely decisions are the top-ranking CSFs. In view of these findings, the study highlighted the key areas for successful implementation of construction projects in Lithuania.